Development and validation of a clinical prediction score (the SCOPE score) to predict sedation outcomes in patients undergoing endoscopic procedures. Issue 1 (11th May 2014) - Braunstein, E. D.; Rosenberg, R.; Gress, F.; Green, P. H. R.; Lebwohl, B.
Summary Background Use of anaesthesia services during endoscopy has increased, increasing cost of endoscopy. Aim To identify risk factors for and develop a clinical prediction score to predict difficult conscious sedation. Methods We performed a retrospective cross‐sectional study of all patients who underwent oesophagogastroduodenoscopy (OGD) and colonoscopy with endoscopist‐administered conscious sedation. The endpoint of difficult sedation was a composite of receipt of high doses (top quintile) of benzodiazepines and opioids, or the documentation of agitation or discomfort. Univariate and multivariate analyses were performed to measure association of the outcome with: age, sex, body mass index (BMI), procedure indication, tobacco use, self‐reported psychiatric history, chronic use of benzodiazepines, opioids or other psychoactive medications, admission status and participation of a trainee. A clinical prediction score was constructed using statistically significant variables. Results We identified 13 711 OGDs and 21 763 colonoscopies, 1704 (12.4%) and 2299 (10.6%) of which met the primary endpoint, respectively. On multivariate analysis, factors associated with difficulty during OGD were younger age, procedure indication, male sex, presence of a trainee, psychiatric history and benzodiazepine and opioid use. Factors associated with difficulty during colonoscopy were younger age, female sex, BMI <25, procedure indication, tobacco, benzodiazepine, opioid and other psychoactive medication use. A clinical prediction score was developed and validated that may be used to risk‐stratify patients undergoing OGD and colonoscopy across five risk classes. Conclusions Using the Stratifying Clinical Outcomes Prior to Endoscopy (SCOPE) score, patients may be risk stratified for difficult sedation/high sedation requirement during OGD and colonoscopy.